Social media and its impact on the social values of the youth in the city of Sulaymaniyah (A research study extracted from a Master's thesis) - کریم, چیا انور حمە کریم حمە; الدین, آ.م.د. جوان جلال الدین محی الدین محی (Sulaimani Journal for Humanities, 2025)
This study aims to identify the most significant effects of social media use on the social values of young people in Sulaimani. This descriptive study utilized a field survey methodology for a non-random, intentional sample of (٣٠٠) young people. The survey instrument was used to obtain accurate data and information related to the study's questions. The study reached a number of conclusions, the most important of which are: (A large portion of young people in Sulaymaniyah use social media at a high level. Family issues are more important to young people than other social issues on these networks. Furthermore, the degree of influence of social media platforms, such as Facebook, was the most significant among the study sample. Finally, the study sample's opinions varied regarding the use of social media and its impact on their social values, but the loss of social trust ranked first).
Keywords: Social Media; Influence; Social Value; Youth; Sulaymaniyah